Prenatal Diagnosis of Zellweger Syndrome: Case Report - Bilgin Kütükcü; Meral Topçu; Sinan Beksaç; Ronald J. Wanders (Gynecology Obstetrics & Reproductive Medicine)
Zellweger syndrome (ZS) (Cerebro-Hepato-Renal syndrome) is a rare autosomal recessive disorder characterized by an absence or marked decrease in peroxisomes, resulting in profound muscular hypotonia and death in the neonatal period. The clinical presentation of ZS is dominated by craniofacial dysmorphic features, neurological abnormalities, hepatomegaly, and chondrodysplasia punctata. Prenatal diagnosis is possible by analysis of dihydroxyacetone-phosphate acyltransferase (DHAPAT) activity, which catalyzes the first step in the biosynthesis of ether-phospholipids, in chorionic villi or amniotic fluid cells. We report the prenatal diagnosis of three pregnancies of a mother who had lost two children previously due to ZS.